Selected performance of alkali-activated mine tailings as cementitious composites: A review. (1st June 2022) - Akinyemi, Banjo A.; Alaba, Peter Adeniyi; Rashedi, A.
Abstract: There is presently a global surge in the demand on extractive industries for their product, which is associated with extraction, processing, and production of valuable minerals through mining activities. During the extraction, huge volumes of the remaining constituents are wastes, which are regarded as mine tailings. These tailings are most times stored in retention ponds or dams leading to serious ecological and environmental challenges due to their hazardous contaminants. Therefore, it is essential to mitigate the effects of mining activities through appropriate utilization of the tailing wastes in the construction industry. One of the major advantages to encourage the reuse of mine tailings is in their mineralogical makeup which favors alkali activation in combination with other materials. This review presents the possible utilization and application of mine tailing wastes as a building material through alkali activation to make an eco-friendly binder. The study covers state-of-the-art information on different sources of mine tailings and the main chemical compounds needed as a binder for the construction industry. A critical review was also performed on the alkali activation synthesis of mine tailings and the composites got from it. The physical, chemical, mechanical properties and microstructural characterization of some of alkali-activated mine tailing composites were similarly considered. Salient issues associated with its use as cementitious materials such as durability, limitations, and sustainability were not overlooked. It is believed that this state-of-the-art review will provide valuable information for researchers, administrators, and students dealing with wastes from various mining activities. Graphical abstract: Image 1 Highlights: Tailings storage in retention ponds or dams can cause serious environmental challenges. Tailings usage is encourage because the mineralogical makeup favors alkali activation. Eco-friendly binder can be produced from tailings through alkali activation. The properties of some of alkali-activated mine tailing composites were reviewed.